The Impact of Social Indicators of Economic Freedom and Poverty on Greece’s GDP Index - Anastasiou, Athanasios; Komninos, Dimitrios; Dermatis, Zacharias; Liargovas, Panagiotis (Technium Social Sciences Journal, 2020)
Socio-economic indicators are usually complex indicators, i.e. they are derived from the composition of individual indicators using a method of weighting. The index of economic freedom shows us how open and friendly our country is towards ’business’. The poverty index is an indication of the standard of living of our country and it is generally considered that it can effectively reflect the various shortcomings of the population. GDP, respectively, measures, in units of money, all finished products produced annually in an economy and traded through the market. Annual GDP growth over a given period is a measure of growth. This economic growth is currently one of the most dynamic growing branches of economic science. In the research section of this paper, we examine the degree of correlation between the social indicators of Economic Freedom and Poverty with the Gross Domestic Product (GDP) financial indicator, and finally, the conclusions drawn from the processing of the correlational data are recorded for future study.